The impact of removing financial incentives from clinical quality indicators: longitudinal analysis of four Kaiser Permanente indicators. (11th May 2010) - Lester, Helen; Schmittdiel, Julie; Selby, Joe; Fireman, Bruce; Campbell, Stephen; Lee, Janelle; Whippy, Alan; Madvig, Philip
Abstract : Objective To evaluate the effect of financial incentives on four clinical quality indicators common to pay for performance plans in the United Kingdom and at Kaiser Permanente in California. Design Longitudinal analysis. Setting 35 medical facilities of Kaiser Permanente Northern California, 1997-2007. Participants 2 523 659 adult members of Kaiser Permanente Northern California. Main outcomes measures Yearly assessment of patient level glycaemic control (HbA1c <8%), screening for diabetic retinopathy, control of hypertension (systolic blood pressure <140 mm Hg), and screening for cervical cancer. Results Incentives for two indicators—screening for diabetic retinopathy and for cervical cancer—were removed during the study period. During the five consecutive years when financial incentives were attached to screening for diabetic retinopathy (1999-2003), the rate rose from 84.9% to 88.1%. This was followed by four years without incentives when the rate fell year on year to 80.5%. During the two initial years when financial incentives were attached to cervical cancer screening (1999-2000), the screening rate rose slightly, from 77.4% to 78.0%. During the next five years when financial incentives were removed, screening rates fell year on year to 74.3%. Incentives were then reattached for two years (2006-7) and screening rates began to increase. Across the 35 facilities, the removal of incentives was associated with a decrease in performance of about 3% per year on average for screening for diabetic retinopathy and about 1.6% per year for cervical cancer screening. Conclusion Policy makers and clinicians should be aware that removing facility directed financial incentives from clinical indicators may mean that performance levels decline.